Associations between cognition, Aβ, and tau in adults with Down syndrome. (December 2021) - Tudorascu, Dana L.; HartleyZammit, Sigan L.Matthew D.; Cody, Karly Alex; Laymon, Charles M.; Minhas, Davneet S.; Zaman, Shahid; Ances, Beau M.; Mathis, Chester A.; Klunk, William E.; Johnson, Sterling C.; Handen, Benjamin L.; Christian, Bradley T.; et al.
Abstract: Background: Adults with Down syndrome (DS) are widely affected by AD pathology by their 30's and have a 70‐80% chance of clinical dementia by their 60's. The aim of the present study was to explore the relationship between cognitive decline and tau pathology using a regression model to explore the associations between longitudinal rates of cognition and the cross‐sectional tau burden in adults with DS. Method: Ninety‐two participants (age=39.19±8.44 at time of tau scan) with DS with multiple cognitive assessments over a period of 9 years, PiB scans over a period of 8 years, and one [18F]AV‐1451 scan were analyzed. Cognitive assessments included tests of overall function (DSMSE), memory (cued recall), executive function (Stroop), and motor function (Purdue pegboard). FreeSurfer (v5.3.0) was used for the definition of ROIs. A two‐stage analysis was performed for cognition and AV‐1451 correlations or PiB and AV‐1451 correlations: 1) a linear mixed model was applied to estimate the rates of change for cognitive outcomes or PiB over time and 2) the cognitive or PiB estimated rates from the trajectories were used as predictors of interest in a correlation analysis with AV‐1451 for each Braak‐associated (1‐6) region as the outcome. Result: Statistically significant associations were found between AV‐1451 retention in all Braak regions and cognitive assessments at alpha=0.05, including cued recall, DSMSE, and the Purdue pegboard task, but not for the Stroop test (Table 1). Statistically significant associations were also found in Braak regions 3‐6 at alpha=0.05 between longitudinal PiB estimated amyloid trajectories and cross‐sectional AV‐1451 retention. Conclusion: For this DS population, we found inverse associations between rates of neuropsychological decline and higher tau pathology. In particular, decline in global cognition, verbal memory and motor function were all associated with higher tau pathology, while executive function was not. Further, longitudinal analyses demonstrated an association between cross‐sectional and accumulating amyloid pathology with increased tau pathology in regions associated with higher Braak stages.